2021
DOI: 10.1002/ajcp.12518
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Practices: Insights from a High‐Quality Math Afterschool Program Serving Underprivileged Latinx Youth

Abstract: High‐quality afterschool programs (ASPs) are opportunities to diversify the ways that Latinx youth from economically underprivileged communities experience STEM learning. Utilizing qualitative methods, based on the experiences and perspectives of low‐income Latinx middle school participants of a math enrichment ASP in Southern California, we identified four culturally responsive practices: (1) the promotion of an inclusive, safe, and respectful program climate, (2) engaging in personal conversations, (3) facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In recent years, researchers have begun calling for culturally responsive mentoring, or mentoring that centers on the lived experiences of those being mentored [52,53]. Mentoring is a well-established practice used to support college students, but more information about how to best provide mentorship is sorely needed [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have begun calling for culturally responsive mentoring, or mentoring that centers on the lived experiences of those being mentored [52,53]. Mentoring is a well-established practice used to support college students, but more information about how to best provide mentorship is sorely needed [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…In a large archival BBBSA sample ( N = 82,224 mentoring matches), Lyons and Edwards (2022) found that matches with shared racial backgrounds were less likely to end prematurely, especially for Black youth. Finally, Yu et al (2021) presented qualitative findings from a STEM mentoring program for Latinx middle‐schoolers, in which most (but not all) mentors were also Latinx, and activities primarily occurred in group settings. In interviews, youth expressed value in having access to mentors from both shared and differing cultural backgrounds.…”
Section: The Importance Of Relationship Quality and Lengthmentioning
confidence: 99%
“…Additionally, group mentoring, which is relatively understudied compared to one‐to‐one mentoring, may provide another viable alternative (Kuperminc & Deutsch, 2021). As reflected in Yu et al's (2021) qualitative findings, an advantage of group mentoring is that youth are often exposed to multiple mentors and peers, giving them opportunities to bond within and across various cultural identities.…”
Section: The Importance Of Relationship Quality and Lengthmentioning
confidence: 99%
“…Informal learning offers an ideal opportunity to connect learning to students’ experiences and identities because there is increased instructional flexibility, and the stakes are lower than in a traditional classroom . This work aims to present an interactive activity to sort recycled waste and assess its impact on students’ understanding of plastic sorting and recycling.…”
Section: Introductionmentioning
confidence: 99%